A detailed study of persons admitted to the spinal unit of conradie hospital, Pinelands, Cape, during 1985. - KETTLES_AN (Department of Health Sciences Education, 2023)
Part I of this study has highlighted certain aspects pertaining to the patients admitted to the Spinal Cord Unit at the Conradie Hospital, Pinelands, with Spinal Cord Injury (s.c.i.). The main points of interest are as follows: 0 The majority of victims of s.c.i. in this series are young men, mainly Black or Coloured, with a low educational and poor employment status, with little in the way of pension or sick leave benefits. 0 Post injury employment opportunities are very limited, as are vocational training facilities. 0 The main causes of injury are examined, and while Motor Vehicle Accidents, Falls and Gunshot wounds are commonly described in the literature as causes of s.c.i., what is unique at the Conradie Hospital is the high percentage of stab wounds (29,6%) causing spinal cord lesions. 0 The method of injury in patients coming from Cape Town is compared and contrasted with the methods of injury in other areas. 0 The levels of the cord lesions and the clinical sequelae are analysed, and while Tetraplegia and Paraplegia are well described in all series on spinal cord injuries, this series is unique in the large number of Brown-Sequard type lesions (36, or 12,7% of all patients) that exist, associated with the large number of stab wounds.